Mauritianism or the mitigated euphoria of the rainbow nation - Dewoo, Moshumee Teena (African Studies, 2015)
Extensively hailed as an economic miracle, an irrefutable ile durable that even defies until today the extrapolations and predictions of the greatest of writers such as Trinidadian V.S. Naipaul about the economic status of the country after it achieved independence, Mauritius has also grown to be known as the archetypal independent state, nurturing a rainbow nation, enn nation larkansiel. Indeed, one cannot deny such glimpses of Mauritianism, where all come together, "as one people, as one nation", as enn sel lepep, enn sel nation to celebrate the island and to celebrate their Mauritianism, their perhaps-hybrid identities and their unique modes of identification. It is undeniable that, to a certain extent, lines of ethnic and cultural differences have become indistinguishable through cultural assimilation, national events, inter-ethnic marriages and post-independence socio-economic relationships, giving Mauritians the appearance of being "one people". However, whilst the island's movement to a stable and successful economy is obvious, observable and is recognised around the globe, the official discourse of a peaceful multiethnic space, a unified multicultural nation proves limited, is mostly mystical, is outdated, if not deceptive of national Mauritian realities: Mauritianism (the rainbow nation) is not described in its authentic, scientific and complete form, but is interpreted and represented, is mystified, kept romantic, euphoric, poetic, inexplicable, and remains narrow. The Mauritian aspiration to the rainbow nation, as well as progressive co-habitation, reciprocal exchanges and the related socio-economic and political matters (what Mauritians experience) seem to have been simplified, if not misidentified as accomplished non-ethnic and future-oriented national unification and homogeneity (what is depicted of the Mauritian people in much of foreign – and archaic - scholarship and other narratives about the island's social stature). The multicultural Mauritian nation and its development, known to Mauritians and explained by local authors, are far more nuanced and complex than the hypothetical, the imagined, exultant, extraordinary and completed rainbow nation' that is praised by many within and beyond Mauritius, and that is envied by those larger nations that have not yet made their multicultural origins a socio-economic asset towards progress and prosperity. It can be argued, therefore, that although not completed, Mauritianism is a possibility sustained mainly in the imaginaries, especially those of non-Mauritians, that the idyllic Mauritian nation is an imagined community. Writing from an experiential point of view, a Mauritian perspective15, would thence contribute to the understanding and explanation of the 'less euphoric', the actual, the physical, the tangible Mauritian nation, perhaps not in its entirety, but at least in its progression, its other realities, its various waves, its challenges and its complexities. Mauritianism, as will be explained in this thesis, is not (yet) a fait accompli, at least not to Mauritians. It remains in many regards an aspiration. What is also interesting, following this logic, is not to look at the consequences of the myth of and the constant aspiration to Chazalian nationalism, but to explore what it claims and possesses, what it interprets and refigures, and what it silences and suppresses.